PENGARUH KEMUDAHAN TRANSAKSI, VARIASI FITUR, DAN KEAMANAN TRANSAKSI DALAM BERBELANJA DI E-COMMERCE SHOPEE TERHADAP LOYALITAS PELANGGAN (SURVEI PADA WARGA VILLA SUKAJAYA INDAH SUKARAMI KOTA PALEMBANG) - Tarissyaa, Uut; Maulana, Chandra Zaky; Asrol, Safitri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Shopee is one of the buying and selling marketplaces that is now in great demand by the public. Research Objectives to determine the effect of Transactions, Feature Variations, and Transaction Security on Shopee Customer Loyalty. This type of research is quantitative. The sampling method is purposive sampling technique and as many as 100 respondents. The data used is primary data. Based on the results of hypothesis testing, it shows that the Ease of Transaction with a value (t-count 3.039> t-table 1.984, and a significant value of 0.003 <0.05), Feature Variety with a value (t-count 2.341> t-table 1.984, and a significant value of 0.021 <0.05), and Transaction Security with a value of (t-count 3.718> t-table 1.984, and a significant value of 0.000 <0.05) have a positive and significant effect on Shopee Customer Loyalty for residents of Villa Sukajaya Indah, Sukarami, Palembang City. And the three variables together have a positive and significant effect with a value of (f-count 7,591> f-table 2,700, and a significant value of 0.000 <0.05) on Shopee Customer Loyalty in residents of Villa Sukajaya Indah, Sukarami, Palembang.